ANALISIS PENGARUH INFLASI, KURS, UTANG LUAR NEGERI DAN EKSPOR TERHADAP CADANGAN DEVISA INDONESIA - Muchammad Kuswantoro (FEB Universitas Sultan Ageng Tirtayasa, 2017)
“TheAnalysisInfluence of Inflation, Rupiah Exchange Rates, External Debt, and Export in Foreign Exchange Reserves Indonesia”.The main purpose this research is to measure the significant level of Inflation, Rupiah Exchange Rates, External Debt, and Export on Foreign Exchange Reserveboth Partiallyor Simoultanously.This reserach used Ordinary Least Squarefor the monthly data period of 2010-2015 (January-December) years by using time series data. Data analysis techniquethat wasused in this research wasthe multiple regression tests with the test of classic assumption (Normality, Multicollinearity, Heteroscedasticity, and Autocorrelation) and Statistic test(ttes, f testand coefficient determination. The independent variable is Inflation, Rupiah Exchange Rate, External Debt, and Export while the dependent variable is Foreign Exchange Reserves.Based on the analysis, the researcher found simoultanously that Inflation, RupiahExchange Rates, External Debt and Export have significant effect to the Foreign Exchange Reserves. Partially, inflation did not give significant effect to the Foreign Exchange Reserves while RupiahExchange Rates, External Debt and Export have significant effect for Foreign Exchange Reserves. Result of coefficient determination analysis shown that R2 was (0.912565) which means Foreign Exchange Reserves can be explained by Inflation, RupiahExchange Rates, External Debt, and Export (91.25%) while the rest (8.75%) can be explained by other variables which did not include to the variables of this research